Feasibility Study of Fuel Oil and Coal Replacement with Natural Gas in Thailand Context - Nakapreecha, Nitida; Vivanpatarakij, Supawat; Audomvongseree, Kulyos (International Journal of Energy Economics and Policy, 2022)
Natural gas is a viable option to oil-based fuels and coal as it has advantage on reliability, domestic availability and more environmental friendliness. This paper assesses the feasibility of replacing fuel oil and coal with natural gas in Thailand’s industrial sector. The study covers the identification of regulatory limitation, the projection of fuel demand and prices, and the assessment of financial and economic feasibility of the fuel replacement project. The financial feasibility study shows interesting investment opportunities only for fuel oil users located within 50 kilometers from the compressed natural gas distribution center. On the contrary, the economic feasibility study shows that there is an outstanding value for investment, particularly for the coal replacement. Consequently, it needs strong measures from the government to drive the replacement. The results of the study are expected to be beneficial in energy management and planning for industrial enterprises. They are also expected to assist the government in developing policies to support the country’s long-term demand for natural gas.